Kajian Literatur Review : Analisis Perbandingan Integrasi Virtualisasi OS terhadap Efisiensi Sumber Daya Komputasi - Aurylia Taffana; Agung Arya Anggara; Bayu Tri Rahayu; Taufiqurrahman Taufiqurrahman; Jajang Kusnendar (Jurnal Publikasi Teknik Informatika, 2025)
The development of operating system virtualization technology has become a crucial need in the computing world to optimize the utilization of resources such as CPU, memory, and application response time. However, resource efficiency in each virtualization technology, including bare-metal, hypervisor, and container, remains a debated topic regarding optimal performance and resource usage. This study aims to analyze the computational resource efficiency of various virtualization technologies, focusing on CPU usage, memory consumption, and application response time. The method used is a descriptive literature review based on 23 relevant accredited national journals and articles. Data were analyzed through classification and comparison of previous research results on virtualization technology performance. The findings indicate that containers have the highest efficiency in CPU and memory usage as well as fast application response times, while hypervisors provide good isolation and security but with higher resource consumption. Bare-metal offers stable performance but with the largest resource usage. The implications of this study provide practical references for system developers and institutions in selecting virtualization technologies that suit resource efficiency needs and serve as a basis for further research in optimizing virtualization technologies.